Grant Financing of Metropolitan Areas : A Review of Principles and Worldwide Practices - Shah, Anwar (World Bank, Washington, DC, 2014)
In the new information age in the globalized and interconnected world, metropolitan areas hold the key to the future prosperity and growth of nations. This paper takes a closer look at grant-financing regimes faced by metropolitan areas and their role in facilitating or hindering improvements in economic and social outcomes of residents of metropolitan areas. A review of 42 large metropolitan areas worldwide shows that, with a few notable exceptions, metropolitan areas in general are hamstrung from playing their potential role in economic advancement. Metro areas have large economic bases and therefore little a priori needs for grant financing, yet they have strong dependence on central transfers. This is because of the highly constrained fiscal autonomy given to these areas, especially in developing countries, with the singular exception of metro areas in China. Such a strong reliance on transfers undermines local autonomy and local accountability. General purpose transfers are formula based , transparent and predictable yet they discriminate against metropolitan areas as they utilize a one size fit all (common formula) for all local governments -- large or small. Such formula typically incorporate equal per jurisdiction component that discriminates against large metropolitan areas. Compactness is rarely rewarded and the greater needs of metro areas for transportation, education, health, culture and welfare go unrecognized. Overall the emphasis in grant financing of metro areas deals with vertical fiscal gaps or project based specific purpose grants. To ensure that metropolitan areas can play their dual roles in improving economic and social outcomes for residents, it is important to strengthen their fiscal autonomy while at the same time enhancing their accountability to local residents. The paper argues that results based grant financing of social and transportation services and tournament based approaches to encourage inter-jurisdictional competition need to be given serious consideration to ensure metropolitan autonomy while strengthening citizen based accountability.